Political fragmentation and projected tax revenues: evidence from Flemish municipalities; Politische Zersplitterung und erwartete Steuereinnahmen: Empirische Belege aus flämischen Gemeinden - Stijn Goeminne; Benny Geys; Carine Smolders (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
The level of revenues pocketed by a government during the fiscal year often deviates from that projected by this government in its budget. Despite a flourishing literature on, for example, the technical or procedural determinants of such forecast errors, little is yet known about how political stratagems may affect forecast errors. In the present paper, we analyse whether differences in the level of government fragmentation are useful in explaining local government tax revenue forecast errors – controlling for various other factors. Using data on 242 Flemish municipalities for the period 1992-2002, we find that two-party governments are more optimistic than single-party governments. In contrast to our initial expectations, governments with at least three parties are significantly more careful (or less optimistic) in their revenue projections than single- or twoparty governments. – – Die Einnahmen einer Regierung während eines Steuerjahres weichen oft von den vorherigen Budgetkalkulationen dieser Regierung ab. Diese Prognosefehler sind zwar schon bezüglich ihres technischen und institutionellen Kontextes empirisch erforscht worden, allerdings fehlt es bisher an Kenntnissen, was den Effekt politischer Variablen betrifft. In der vorliegenden Veröffentlichung wird untersucht, ob die politische Fragmentierung der lokalen Regierungen einen wichtigen Faktor zur Erklärung von Prognosefehlern darstellt, dabei immer kontrollierend für verschiedene andere Elemente. Unsere empirische Analyse von 242 der 308 flämischen Gemeinden im Zeitraum 1992-2002 zeigt erstens, dass Regierungen mit zwei Parteien eher optimistisch ihr Budget planen. Sie setzen mehr Einnahmen voraus, als sie während des Steuerjahres bekommen. Im Gegensatz zu unserer Hypothese zeigt die Analyse aber auch, dass ab 3 Parteien in einer Regierung die Überschätzung der Einnahmen geringer wird.
Keywords: D72; H72; H79; 330; Revenue projections; forecast accuracy; local taxation; Flemish municipalities; government fragmentation